Analysis of the effect of price and money supply on economic growth in Ghana - SAEED, Abdul-Razak Abass (KDI School, 2022)
Economies all over the world aim to achieve high growth rate of output and stability in the general price level. But the tradeoff between output growth and inflation makes it imperative for Central Banks to conduct monetary policy. The study, therefore, aims to analyze the effect of price and money supply on GDP growth in Ghana using a forty-year time series data from 1980 to 2020. The empirical work used Vector Error Correction Model (VECM), cumulative impulse response function in VAR model and causality checks techniques to assess short-run and long- run relationship among price level, broad money supply, interest rate and GDP. Analysis of VECM short-run estimates revealed broad supply of money significantly affects GDP. The results further indicate that past year income and price level have negative and statistically significant effects on current year output. However, long-run estimates of the co-integrating vector shows that supply of money does not have statistically significant effect on GDP. This result is corroborated by the outcome of the cumulative orthogonal impulse response function. Furthermore, with -0.215 as the coefficient of the error correction model, a disequilibrium to GDP caused by shocks to the exogenous variables in the short-run are corrected at an adjustment speed of 21.5% in the long-run. Moreover, the study robustly concludes on bidirectional relationship between inflation and money supply. As a policy recommendation, this study proposes that the Bank of Ghana pays critical attention to the monetary policy rate since it is the channel through which the central bank targets inflation in order to achieve price stability and sustained output growth.
Thesis(Master) -- KDI School: Master of Public Policy, 2022
Keywords: Interest rates--Ghana; Economic development--Ghana; Monetary policy